The Kashmiri diaspora remembers the displacement: Implication and the challenge of healing - Razdan, Aditi (Memory studies, 2024)
From 1989 to 1991, the majority of Kashmiri Pandits (Hindus) were displaced from their home in the Muslim-majority Indian-administered Kashmir Valley, in a crisis which I refer to as the displacement. The period that has followed in the Kashmir Valley has been marred by heavy military presence and state violence against Kashmiris – mostly Muslim – who have remained in Kashmir. More than three decades later, Kashmir is still a contested region; memories of the displacement are unreconciled and its diaspora remains divided. This article reveals how memory-work through storytelling can impede reconciliation processes by reinforcing enduring narratives of marginalisation. These enduring narratives frame contemporary memory-making and prevent groups from seeing their implication in oppressive structures. Drawing on Kashmiri conceptual paradigms and oral history interviews with Kashmiri Pandit and Muslim diasporic communities in Australia, I examine both what Kashmiri Pandit and Muslim diaspora share, and why they find it hard to take on the narrative perspective of the other side. While Pandits and Muslims draw on a shared Kashmiri repertoire, they locate themselves very differently within this narrative past. As such, neither Pandits nor Muslims find it easy to see how they are implicated in the direct and structural forms of violence that led to the displacement and subsequent acts of violence. These historical narratives, transmitted through oral stories, may disrupt attempts to institute reparative processes in Kashmir. By analysing this archive of Kashmiri diasporic memory, I argue that this case study complicates our assumptions that personal narratives, particularly in memory-work, are activist vehicles that offer a pathway to healing.